2021
DOI: 10.2214/ajr.21.25581
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ultrasound and MRI in Diagnosis of Severe Placenta Accreta Spectrum Disorder: An Intraindividual Assessment With Emphasis on Placental Bulge

Abstract: The publication of this Accepted Manuscript is provided to give early visibility to the contents of the article, which will undergo additional copyediting, typesetting, and review before it is published in its final form. During the production process, errors may be discovered that could affect the content of the Accepted Manuscript. All legal disclaimers that apply to the journal pertain. The reader is cautioned to consult the definitive version of record before relying on the contents of this document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
(68 reference statements)
0
15
1
Order By: Relevance
“…In a different study, Gulati et al found that Doppler US could be used as an important tool for the detection of bridging vessels, which had a high specificity (93.5%) for PAS [ 33 ], which was comparable to our study (Sp-92.3%). On the other hand, in our study, placental bulging presented a very low sensitivity (30.7%) and a maximum specificity, while other authors reported good sensitivity (91.7%) and poorer specificity (76.9%) [ 34 ].…”
Section: Discussioncontrasting
confidence: 84%
“…In a different study, Gulati et al found that Doppler US could be used as an important tool for the detection of bridging vessels, which had a high specificity (93.5%) for PAS [ 33 ], which was comparable to our study (Sp-92.3%). On the other hand, in our study, placental bulging presented a very low sensitivity (30.7%) and a maximum specificity, while other authors reported good sensitivity (91.7%) and poorer specificity (76.9%) [ 34 ].…”
Section: Discussioncontrasting
confidence: 84%
“…The main MRI features of accreta placentation include abnormal uterine bulging, dark intraplacental bands on T2-weighted imaging, heterogeneous signal intensity within the placenta and disruption of the uteroplacental zone [40][41][42][43][44][45][46][47][48] . Recent data suggest that the finding of a placental budge on MRI has the highest sensitivity for the diagnosis of severe PAS 43 . However, as a placental bulge is a hernia of placental tissue through a dehiscence of the uterine wall and is independent of accreta placentation (Table 1), this sign is unlikely to add much to the prenatal diagnosis of PAS.…”
Section: Prenatal Imaging Diagnosis Of Pasmentioning
confidence: 99%
“…The main MRI features of accreta placentation include abnormal uterine bulging, dark intraplacental bands on T2-weighted imaging, heterogeneous signal intensity within the placenta and disruption of the uteroplacental zone [40][41][42][43][44][45][46][47][48] . Recent data suggest that the finding of a placental budge on MRI has the highest sensitivity for the diagnosis of severe PAS 43 .…”
Section: Prenatal Imaging Diagnosis Of Pasmentioning
confidence: 99%
“…Despite a growing body of evidence to the contrary, the description of PAS as an invasive placental disorder persists and predominates in the current literature and most recent medical society guidelines on this topic. [28][29][30][31][32][33][34][35][36] Even with a recent move away from the use of traditional histopathologic criteria for diagnostic grade (accreta, increta, percreta), current pathologic 22 and clinical 21 grading schemes rely on invasion as a central component of characterizing disease progression. This, in part, has resulted in an inability to sufficiently predict disease severity 37 and morbidity with antenatal imaging.…”
Section: Discussionmentioning
confidence: 99%